Freezability biomarkers in bull epididymal spermatozoa - Ryu, Do-Yeal (Sci Rep, 2019)
Sperm cryopreservation is an important tool for storing genetic traits and assisted reproduction techniques. Several studies have developed semen cryopreservation protocols. However, the sperm proteome is different between ejaculated and epididymal spermatozoa and little is known about cryopreservation effects on epididymal spermatozoa. Therefore, our study aimed to (i) investigate the differences of sperm parameters based on the freezing tolerance of spermatozoa and (ii) identify potential markers to predict the freezability of bull epididymal spermatozoa. Our preliminary study demonstrated that spermatozoa from individual bulls differ in cryopreservation freezability. We categorized spermatozoa into high freezing-tolerant spermatozoa and low freezing-tolerant spermatozoa group based on sperm motility after freezing/thawing. We evaluated several sperm functional parameters, including sperm motility/motion kinematics, sperm speed parameters, viability, mitochondrial activity, and capacitation status. Our results demonstrated that motility, sperm speed parameters, viability, and mitochondrial membrane potential had significant differences between the two groups but motion kinematics and capacitation status did not. In addition, the concentration of three proteins - glutathione s-transferase mu 5, voltage-dependent anion-selective channel protein 2, and ATP synthase subunit beta, differed between both groups. Thus, our research highlighted differences in bull epididymal spermatozoa freezability upon cryopreservation and these proteins might be useful markers to select high freezing-tolerant epididymal spermatozoa.